Molecular architecture of the human GINS complex. - Boskovic, J; Coloma, J; Aparicio, T; Zhou, M; Robinson, C; Méndez, J; Montoya, G (2007)
Chromosomal DNA replication is strictly regulated through a sequence of steps that involve many macromolecular protein complexes. One of these is the GINS complex, which is required for initiation and elongation phases in eukaryotic DNA replication. The GINS complex consists of four paralogous subunits. At the G1/S transition, GINS is recruited to the origins of replication where it assembles with cell-division cycle protein (Cdc)45 and the minichromosome maintenance mutant (MCM)2-7 to form the Cdc45/Mcm2-7/GINS (CMG) complex, the presumed replicative helicase. We isolated the human GINS complex and have shown that it can bind to DNA. By using single-particle electron microscopy and three-dimensional reconstruction, we obtained a medium-resolution volume of the human GINS complex, which shows a horseshoe shape. Analysis of the protein interactions using mass spectrometry and monoclonal antibody mapping shows the subunit organization within the GINS complex. The structure and DNA-binding data suggest how GINS could interact with DNA and also its possible role in the CMG helicase complex.